GASTROINTESTINAL PARASITISM IN TWO SEASONS IN GUINEA PIGS (Cavia porcellus) OF OXAPAMPA, PASCO - Vargas R., Merly (2014)
The objective of the study was to determine the prevalence of gastrointestinalparasites in the rainy and dry season in guinea pigs (Cavia porcellus) in semi-commercialfarms in Oxapampa, Paso, Peru, as well as to identify the parasite species and to assessthe season and productive phase as risk factors. Two hundred faecal samples per season were collected where the experimental unit was the cage. The samples were processed bythe flotation, sedimentation and modified McMaster methods. The prevalence was 90.0± 4.1 and 63.5 ± 6.7% in the rainy and dry season respectively, and the identified specieswere Paraspidodera uncinata, Trichuris spp, Capillaria spp, and Eimeriacaviae. Onthis, E. caviae and P. uncinata showed the higher frequencies in both seasons. The rainyseason represented a risk of 5.7-fold relative to the dry season, especially for E. caviae(8.2), while the rearing phase represented a risk of 2.2-fold relative to breeding animals,especially for P. uncinata (2.6) and E. caviae (2.5), while breeding animals showed ahigher risk of infection for Capillaria spp (6.2) in relation to the growing animals.